Dinamika collective effervescence dalam peringatan hari raya islam di lingkungan minoritas - Alfrida, Hassya Nailah (Maliki Interdisciplinary Journal, 2026)
This study examines the dynamics of collective effervescence in the celebration of Islamic holidays within minority communities using Émile Durkheim’s sociology of religion perspective. Religion is understood as a system of collective beliefs and practices that strengthens social solidarity through shared emotional experiences. Islamic holidays such as Eid al-Fitr, Eid al-Adha, and Mawlid are not merely religious rituals but also social mechanisms that reinforce identity, strengthen social bonds, and reproduce collective values. In minority contexts, these celebrations hold greater significance as they function as strategies for identity preservation amid assimilation pressures and limited social space. Using a qualitative descriptive approach based on theoretical analysis, this study finds that collective effervescence emerges through physical proximity, uniformity of actions, and shared symbolic focus, resulting in heightened emotional intensity and stronger group cohesion. Furthermore, practices such as interfaith philanthropy and social adaptation demonstrate that these celebrations also serve as tools for inclusive social negotiation. Therefore, religious rituals in minority settings not only sustain group identity but also foster harmonious relationships within multicultural societies.